JUHUUD AL-MU’ALLIMIIN FII AL-TARQIYAAH MAHAARAH QIRAA’AH AL-KUTUB AL-SHAFRAA’ FII AL-MA’HAD AL-ISLAAMII KASYF AL-ANWAAR AMUNTAI (AL-I’ROBY: Jurnal Pendidikan Bahasa Arab Dan Kebahasaaraban, 2025)
Reading the kitab kuning is not easy, it requires perseverance and mastery of knowledge of other sciences such as Arabic, nahwu, sharaf and others. An Islamic boarding school are not spared in terms of teaching reading the kitab kuning, including the Kasypul Anwar Amuntai Islamic Boarding School. The kitab kuning reading competition at the district level are wustha (Middle) and Ulya (Upper) levels. The ability of students to read the kitab kuning cannot escape the education and guidance of teachers. This is because teachers have a role in the teaching and learning process. This research method uses descriptive qualitative the results of this study are: 1) Teachers' efforts to improve the skills of reading the kitab kuning for students at the Kasypul Anwar Amuntai Islamic Boarding School are: (a) The use of several types of methods during teaching, namely the bandongan, sorogan and question and answer methods. (b) providing motivation for students in the form of inspirational stories, and educational humor. (c) invite students to pray together before and after learning; 2) The difficulties are, (a) the lack of concentration of some students during learning because they are sleepy. (b) some students sometimes forget the rules of Nahwu and Sharaf.